If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + -5x = -8(6 + 2x) 7 + -5x = (6 * -8 + 2x * -8) 7 + -5x = (-48 + -16x) Solving 7 + -5x = -48 + -16x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '16x' to each side of the equation. 7 + -5x + 16x = -48 + -16x + 16x Combine like terms: -5x + 16x = 11x 7 + 11x = -48 + -16x + 16x Combine like terms: -16x + 16x = 0 7 + 11x = -48 + 0 7 + 11x = -48 Add '-7' to each side of the equation. 7 + -7 + 11x = -48 + -7 Combine like terms: 7 + -7 = 0 0 + 11x = -48 + -7 11x = -48 + -7 Combine like terms: -48 + -7 = -55 11x = -55 Divide each side by '11'. x = -5 Simplifying x = -5
| -3x+10x= | | 3(4-2x)=-2(4x-1) | | -6(-2-2g)= | | 5x+2X-3= | | 4x+y^2=12 | | 2a+4-8a-19= | | -18-6= | | 2(6m+8)= | | 6(10+10g)+2= | | z+(-7)=-5 | | 2ln(x+1)=ln(1-2x) | | .42-1.2=.3r+.6 | | X+11=3x+31 | | 2h=d | | 2(1+8a)+8a= | | 3x-35=125 | | w+6=-9 | | 9m-3m(m+6)=2(m+1) | | -5(-2t+-8)= | | 2.5x-5+8=19.5 | | 0.5n-6=12 | | -1.5x+y=1 | | -1.5+y=1 | | 5(6x-3)=3(8x+1) | | 15x=6y-9 | | -9+7k+8(7+10k)= | | 2(x-2)=x+3 | | y-1.5=1 | | 3x+2x+5=10(x+1) | | 891.25=x(7.5+4.75) | | 22+2s=10+5s | | 22+2s=1 |